69.8k views
5 votes
How do I solve this equation by using the quadratic formula 3x^2-12x-27=-6

2 Answers

3 votes

Explanation:

The quadratic equation is

x=−b=−√b2−4ac2a

for a quadratic taking the form

ax2+bx+c=0

So for this equation it is

x=−(−12)±√(−12)2−4⋅3⋅112⋅3

x=12±√144−1326

x=12±√4⋅36

x=6±√33

User Jaeeun Lee
by
5.2k points
5 votes

Answer:

Move all terms to the left side of the equation and simplify.

3x²−12x−21=0

Use the quadratic formula to find the solutions.

(−b±√b²−4(ac))/2a

Substitute the values a=3, b=−12, and c=−21 into the quadratic formula and solve for x.

(12±√(−12)²−4⋅(3⋅−21)0/2⋅3 Simplify => x=2±√11

The result can be shown in multiple forms.

Exact Form: x=2±√11

Decimal Form: x=5.31662479…,−1.31662479…

Explanation:

User SanketR
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.